THE INFLUENCE OF COMPETENCE, INDEPENDENCE, AND AUDITOR’S PROFESSIONAL ETHICS ON AUDIT QUALITY - Colette, Ashley Eugenia; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2024)
Having responsibility to the public is what makes auditor’s capabilities and characteristic essential to providing a quality audit service. This study aims to gather empirical evidence on how the quality of audit produced is influenced by competence, independence, and professional ethics of auditor. This research was conducted through distribution of questionnaires to auditors working in public accounting form based in Jakarta. The result shows that auditor’s competence, independence, and professional ethic has a positive influence on the resulted audit quality, however the influence of auditor’s independence is shown to be insignificant. To sum up, the competence and ethics of an auditor have an influence on the quality of an audit, but auditor independence has no influence on audit quality. The implications of this study that Public accounting firms can improve the professionalism of their auditors through high levels of competency with continuous learning and practice supported by ethics.